(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
The purpose of this article is to address the judgments of the Federal Supreme Court (STF) on the declaratory action of constitutionality (ADC) and direct actions of unconstitutionality (ADIs) filed against the provisions of the current Forest Code (Law no. 12. 651/2012), especially with regard to the articles that reduced environmental protection in relation to the previous Forest Code (Law no. 4.771/1965), with the aim of analyzing the impacts of these judgments, in concentrated control of constitutionality, especially after they have become final and binding. The study uses a descriptive-analytical methodology, with a qualitative approach, centered on bibliographical research and an examination of the STF ’s case law , in order to verify the effects of these decisions. The topic is relevant and topical insofar as the different instances of the Judiciary are still awaiting judgment on the necessary remittances, appeals and complaints in which they are analyzing whether or not to overcome the understanding of the Superior Court of Justice (STJ), based on the principles of tempus regit actum and the prohibition of environmental retrogression, which is intended to prevent the application of provisions of the current Forest Code, whose unconstitutionality was not recognized by the STF. In the end, we conclude that the Courts, including the STJ and other courts, must comply with the STF’s decisions in ADIs/ADCs, and that complaints can be filed against decisions to the contrary, in order to enforce the Supreme Court’s decisions, in judgments that have become final and binding. In addition, this understanding has been applied to a matter within the jurisdiction of the Federal Regional Court of the 3rd Region regarding the regulation of permanent preservation areas around artificial reservoirs for the supply and generation of electricity.